Enhanced Detection of Recurrent Diffuse Malignant Peritoneal Mesothelioma Using 68Ga-FAPI PET/CT Compared to 18F-FDG PET/CT: A Case Report - Abdulrahman, Marwah; Al-Rasheed, Ula; Dabous, Ali; Al-Ibraheem, Akram (World Journal of Nuclear Medicine, 2025)
Diffuse malignant peritoneal mesothelioma (DMPM) is a rare and aggressive subtype of epithelioid mesothelioma that arises from the lining of the abdominal cavity. While the applications of traditional fluorine-18 fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) in diagnosis and staging of DMPM are well-established, the utility of gallium-68 fibroblast activating protein inhibitor (68Ga-FAPI) PET/CT in detecting disease recurrence remains an area that requires further research and validation, with limited literature. Implementing FAPI PET/CT for these cases may provide superior lesion detectability and higher reporter confidence, prompting the need for further studies to investigate the potential future role of FAPI theranostics in guiding treatment decisions for DMPM. This case report describes a 49-year-old male patient diagnosed with DMPM, who underwent cytoreductive surgery and hyperthermic intraperitoneal chemotherapy but developed recurrent disease that was better visualized on 68Ga-FAPI PET/CT compared with 18F-FDG PET/CT.
Keywords: FAPI; DMPM; malignant peritoneal mesothelioma; 68Ga-FAPI PET/CT; FAPI theranostics